Community-based post-disaster recovery strategies and innovations the experiences from Southern Cebu, Philippines. - Arreglo, John Carlou; Belamia, Angelie Ann P.; Canillo, Christine Joy L.; Dungog-Cuizon, Ana Leah; Casili, Charmagne Angelie C.; Fajardo, Kristine Angelika T. (Cebu City College of Social Sciences, University of the Philippines Cebu, 2023)
Community participation in post-disaster recovery has been widely undermined in contemporary society. Existing literature on disaster recovery shows less consideration of the critical role of the community, while the government?s post-disaster recovery planning lacks community representation. Planning for disaster mitigation and recovery in the Philippines is heavily centralized within government institutions with little emphasis placed on community involvement. However, the country's experiences from past disasters demonstrated that community participation in post-disaster efforts is critical to the overall recovery processes. Thus, anchored in this backdrop, this study particularly aimed to determine the various community-based post-disaster recovery strategies and innovations manifested in the municipalities of Sibonga, Argao, and Dalaguete in Southern Cebu, Philippines after Typhoon Rai, locally known as supertyphoon Odette, hit the country on December 16, 2021. The researchers utilized a descriptive qualitative research design to identify and examine the different factors that motivated the communities to organize themselves and initiate post-disaster recovery strategies. Group discussions and one-on-one interviews with the municipal DRR coordinator, elected officials, and residents were utilized to gather significant data. Using the three municipalities?Sibonga, Argao, and Dalaguete in Southern Cebu?as the cases in this study, the researchers found out that communities were compelled to take strategic recovery measures post-disaster because of various factors such as inadequacy in government assistance and support which is heavily dependent on systematic disaster financial planning and highly organized structure of the MDRRMO. This was further exacerbated due to the politicization of the recovery procedures that impeded the overall disaster recovery process. Whereas, the majority of community initiatives emanated at the grassroots and provided assistance on the psychosocial and mental recoveries of the residents, which the local government units were unable to respond to. Based on the findings of this study, a bottom-up post-disaster recovery governance framework is proposed as a recommendation for systematic and community-centered post-disaster recovery planning.
Thesis (Bachelor of Arts in Political Science) -- University of the Philippines Cebu, January 2023.
Includes bibliographical references and appendices.